Factors determining adoption level of improved sugarcane production technology among farmers in Lakhimpur Kheri district, Uttar Pradesh - Ranjeet Kumar; N.R. Meena; R.K. Doharey; Avneesh Kumar; Sandeep; Kamni Paia Biam; Amit Kumar (Annals of Agricultural Research, 2025)
Sugarcane (Saccharum officinarum L.) is a crucial commercial crop contributing significantly to India’s agricultural economy. Despite its importance, sugarcane cultivation faces major productivity challenges, notably from various biotic stresses. This study was conducted during 2022-23 to assess the adoption level of improved sugarcane production technologies and identify factors influencing adoption among farmers in Lakhimpur Kheri district, Uttar Pradesh. A total of 120 sugarcane growers were selected using a stratified random sampling method. Data were collected through a structured interview schedule and analyzed using appropriate statistical techniques. Findings revealed that 46.6% of respondents exhibited a medium level of technology adoption, followed by high (40.00%) and low (13.3%) adoption levels. Practices such as recommended seed rate (MPS 97.8) and ratooning (MPS 95.7) recorded the highest adoption, while intercropping (MPS 32.4) and seed treatment (MPS 36.42) were among the least adopted. Correlation analysis indicated that education (r = 0.386**), economic motivation (r = 0.464**), and landholding size (r = 0.323**) were significantly and positively associated with adoption levels. Caste (r = 0.284*), family size (r = 0.272*), and scientific orientation (r = 0.212*) also showed significant positive relationships, whereas risk orientation had a significant negative correlation (r = -0.287*). Other variables such as age, marital status, family type, social participation, material possessions, and extension contact were not significantly associated. The study concludes that enhancing education, economic drive, scientific orientation, and mitigating risk aversion through targeted interventions could significantly promote the adoption of improved sugarcane technologies, thereby boosting productivity and sustainability.